ANALISIS KEGIATAN TWC UNTUK MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK - Imanina, Nurin; Pambudi, Bayu Teguh; Wahyuni, Baiq Laeli; Asmaradhana, Ersza Triyoga; Harianti, Mita; Papandriyo, Prela Nuresto; Alfan, Muhammad (Universitas Negeri Malang, 2024)
Education plays a crucial role in enhancing the quality of human resources. One of the efforts to improve the quality of education in schools and thus enhance human resources is the collaboration between teachers and parents, which can boost students' learning motivation. One such effort to enhance students' learning motivation in schools is through the implementation of Three-Way Conference (TWC) activities. TWC is a meeting involving students, parents, and teachers to collectively reflect on students' learning outcomes. The aim of this research is to determine the impact of implementing TWC on students at the Laboratory Junior High School of Malang University. The method employed in this research is literature review. Literature review was obtained through articles or journals relevant to this research. The research findings indicate that the implementation of TWC activities has several impacts, including students gaining a better understanding of their areas of interest, schools inviting parents to the school with different schedules for each parent, teachers being able to follow up on learning activities that can enhance students' learning motivation, and parents providing support to motivate their children further in classroom learning.